Female Agency in the Song ‘Man I Need’ by Olivia Dean: A Systemic Functional Discourse Analysis - Amalia Agatha; Fariq Shiddiq Tasaufy (Hasanuddin University, 2026)
Song lyrics, as a widely consumed form of popular discourse, play a significant role in constructing gender representations and power relations through specific linguistic choices. Yet, limited research has examined female agency through an approach that integrates systemic functional and critical discourse perspectives. This study aims to examine how female agency is discursively constructed in the song